Penguatan Profil Pelajar Pancasila Melalui Pelatihan Pembuatan Handout Untuk Membangun Nalar Kritis Siswa di lingkungan Perguruan Muhammadiyah Kramatjati, Jakarta Timur - Supriansyah; Ruslan, Ahmad; Syae Purrohman, Purnama; Samiah, Wardah (PADMA, 2024)
The profile of Pancasila Students as a translator of the goals and vision of education to a format that is easier to understand by every element in the world of education needs to be considered in every point contained in it, starting from faith and noble character, independence, mutual cooperation, single celebrity, critical and creative reasoning. These six points need to be integrated in learning and non-learning activities. One of the points highlighted is the ability to "reason critically" students, this is considered important because critical reason is an element that must be possessed in facing the modern era in order to sort out the positive and negative things caused by the progress of the times. In this regard, a team from the University of Muhammadiyah Prof. Dr. Hamka conducted training activities with partners from Muhammadiyah Kramatjati College. This training was attended by at least 20 teachers, with the resource persons from this activity being lecturers of Historical Education